A novel electrochemical interdigitated electrodes sensor for limonin quantification and reduction in citrus limetta juice. (1st July 2022) - Das, Satyajit; Sahu, Partha Pratim
Highlights: MgSiO3 ·xH2 O-PVA based interdigitated electrodes capacitive sensor has been developed. The sensor exhibited high sensitivity (nearly 2.392 µF/ppm) with a low response time (nearly 6 secs). It performs quantification as well as debittering of limonin at different stages of juice processing. Reduction of limonin content from 5.77 ppm to 4.29 ppm in citrus limetta juice within 60 s is observed. Abstract: Limonin, a highly oxygenated triterpene biomolecule of citrus fruits is responsible for delayed bitterness of its juice lowering consumer's acceptability. Hence, limonin detection is essential for appropriate debittering intrusions. A novel interdigitated capacitive sensor using magnesium silicate-poly vinyl alcohol (MgSiO3 .xH2 O-PVA) composite has been introduced for quantification of limonin and debittering through selective adsorption of limonin from the citrus limetta juice. The sensor showed high sensitivity of 2.392 µF/ppm and fast response time of ∼6s. The sensor enables both quantification as well as measure debittering of citrus juice showing a reduction in limonin content from 5.77 ppm to 4.29 ppm with an exposure time of 60s to the sensing material making it distinctive in comparison to other methods. The sensor's results were validated with HPLC analysis. The device is simple, low-cost and reusable which promises easy, on-site and rapid quantification and reduction of limonin content in citrus juices without having toxicity.